The Role of the Judicial Branch in Brazilian Rule of Law Erosion - Gabardo, Emerson; Salgado, Eneida Desiree (Revista de Investigações Constitucionais, 2021)
The rule of law is the central milestone of modern democratic states. There is a gap, however, between what is on the constitutional texts and the lived-in world. The scholars use to concentrate their focus on the Executive Branch’s role (and, sometimes, of Legislative Power) in situations of disregard of the Constitution. However, we chose to target the Judicial Branch and its decisions as contributions to the erosion of the rule of law and the production of democratic decay. We claim that the Judiciary started to play a crucial role in this process by assuming a populist bias and carrying out common lawfare practices – which can be well exemplified by judicial electoral decisions and the judicial decisions about Operation Car Wash. For researching the problem and discussing the hypothesis, we used the theoretical-deductive method. We carried out a literature review. We also use informative documentaries extracted from the media on the behavior of public authorities and the critical description of judicial decisions. The bibliography is interdisciplinary. We conclude that when the Judicial Branch becomes a political actor, it fosters a situation of instability and becomes an institution whose legitimacy depends on variations in the mood of society – which goes against the assumptions of democracy and the rule of law. This new judicial behavior causes an imbalance between the powers and the absence of an institution that moderates social conflicts. This situation contributed to the resurgence of the authoritarian identity of Brazilian civil society and the ideological polarization that culminated in the election of a far-right administration in 2018.